South Asian urban experience - Sharma, R. C. 1932- (Criterion Publications, 1988)
Papers presented at the First Regional Symposium "South Asian Urban Experience" organized by the Jawaharlal Nehru University and the Ministry of Urban Development, New Delhi, 20-22 February 1986.